IDENTIFIKASI SOIL TRANSMITTED HELMINT PADA FESES TERNAK BABI MENGGUNAKAN METODE DIRECT SLIDE - Solikah, Monika Putri; Widyastuti, Havida (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Until now, parasitic diseases that infect humans and animals have not been considered in Indonesia because these diseases do not cause clinical symptoms (subclinical). Gastrointestinal disease caused by worm parasites is a systemic disease that attacks the digestive tract of cattle. Traditional pig farming methods and poor hygiene are the main reasons for the spread of zoonoses that can be transmitted from pigs to humans. This study aims to identify nematode hosts by examining worm eggs in pig feces using the direct slide method. From a total of 20 stool samples, 3 samples were positive for nematode worm eggs. A stool sample that is identified as positive for worm eggs determines the level of parasitic infestation. Worm egg detection was carried out in the laboratory of the Faculty of Health Sciences University and analyzed descriptively, then the number of worm eggs was counted to determine the prevalence of endoparasites.